Shunt Technology in Pediatric Neurosurgery: Current options and Scientific Evidence - Luciano Lopes Furlanetti; Matheus Fernando Manzolli Ballestero; Ricardo Santos de Oliveira (Brazilian Society for Pediatric Neurosurgery, 2021)
Introduction: Hydrocephalus is the most common neurosurgical condition among children worldwide and shunt diversion of the cerebral-spinal fluid (CSF) has been widely available. The aim of the present study was to perform a systematic review on types and models of shunt devices available and critically evaluate scientific evidence in favor of the usage of specific technologies. Methods: Searches of the PubMed database were performed for relevant articles published from until March 2020. Appropriate keywords were used to identify all studies, including: "shunt", "technology", "hydrocephalus", "children", "pediatric". The indications and scientific evidence in favor of the usage of specific shunt technology for the treatment of hydrocephalus according to age, underlying pathology and other features of specific patients were discussed under the light of the current literature. Results: A total of 178 peer-reviewed papers were found. Out of them, only 21 matched our inclusion criteria and were finally selected. The papers were reviewed and described technology discussed below. A summary of the main types of shunts commercially available worldwide, including their respective working mechanism and construction was also included. Conclusion:Shunt technology has evolved during the last decades and continues to be intensively developed. Despite of the huge arsenal of different types of shunt systems currently available on the market, the treatment of hydrocephalus remains challenging. Investment in research, education and training, as well as prospective randomized multicentric controlled trials evaluating the role of specific valves in the treatment of individual group of hydrocephalic pediatric patients are urgently needed.